Visual outcomes in relation to time to treatment in neovascular age‐related macular degeneration. (14th June 2015) - Rasmussen, Annette; Brandi, Sara; Fuchs, Josefine; Hansen, Louise H; Lund‐Andersen, Henrik; Sander, Birgit; Larsen, Michael
Abstract Purpose To study the relation between the interval from diagnosis to initiation of intravitreal injection therapy and visual outcome in neovascular age‐related macular degeneration (nAMD) and to report changes over time in fellow‐eye status. Methods Retrospective chart review. The study included 1185 eyes in 1099 patients who began vascular endothelial growth factor inhibitor treatment for nAMD during four separate periods in 2007, 2009, 2011 and 2012 using a fixed loading‐dose regimen of three ranibizumab injections. Results Mean best‐corrected visual acuity (BCVA) at presentation remained within the range 0.23–0.24 Snellen and the median patient age within 79–80 years, whereas BCVA at first visit after the third injection increased from 0.24 to 0.31 (p < 0.0001) in concert with a shift in preferred practice from separate‐day injection to same‐day injection. This led to a reduction in the median time to treatment from 16 days to 1 day. The proportion of patients with fellow‐eye BCVA 0.05 or worse at presentation with newly diagnosed wet AMD in the incident eye decreased from 38% to 22% (p < 0.0018). The proportion of bilaterally treated patients increased during the study period. Conclusion In this study, 2‐week‐earlier injection was associated with the equivalent of a 5‐Early Treatment Diabetic Retinopathy Study letter‐gain in mean visual acuity at 3 months after presentation. The difference is larger than expected from the 2‐week‐longer duration of disease at the study end‐point. The study supports that early diagnosis and treatment of nAMD is of value for functional outcomes.